PENDIDIKAN KARAKTER SEBAGAI UPAYA MEWUJUDKAN PROFIL PELAJAR PANCASILA - RITASARIFIANU LAGHUNG (CENDEKIA: Jurnal Ilmu Pengetahuan, 2023)
The profile of Pancasila students is part of the Ministry of Education and Culture's vision and mission, which is very important to implement in educational institutions, to develop students as Pancasila students, who demonstrate the value of faith, fear of God Almighty and have noble character, critical thinking, global diversity, mutual cooperation, independent and creative. The strategy for developing a Pancasila student profile is carried out through integration in formal education activities through intracurricular, co-curricular and extracurricular activities which are packaged in project activities to strengthen Pancasila student profiles. Through the implementation of the Pancasila student profile policy, it is hoped that it will be able to build the character of Indonesian students who are superior and able to compete globally. This study aims to describe the values of the Pancasila student profile through a series of extracurricular activities and Project activities to strengthen the profile of Pancasila students which are carried out at SMP Negeri 5 Kota Komba. This research is a qualitative research with descriptive qualitative type. Data were collected by document study and interview methods. Data were analyzed by data reduction process, data presentation, and conclusion drawing. The results showed that the value of the Pancasila student profile was applied through mutual cooperation activities, literacy and numeracy activities, religious guidance, flag ceremonies and school cultural gatherings. The profile of Pancasila students is very relevant and related to the Indonesian government's efforts to implement character education at the school level. ABSTRAKProfil pelajar pancasila merupakan bagian dari visi misi kemendikbud, yang sangat penting dilaksanakan pada instansi pendidikan, untuk menumbuhkembangkan peserta didik sebagai pelajar pancasila, yang menunjukkan nilai beriman, bertakwa kepada Tuhan Yang Maha Esa dan berakhlak mulia, bernalar kritis, berkebhinekaan global, gotong royong, mandiri dan kreatif. Strategi pengembangan profil pelajar Pancasila dilakukan melalui integrasi dalam kegiatan pendidikan formal melalui intrakurikuler, kokurikuler dan ekstrakurikuler yang dikemas dalam kegiatan proyek penguatan profil pelajar Pancasila. Melalui implementasi kebijakan profil pelajar Pancasila ini diharapkan mampu membangun karakter pelajar Indonesia yang unggul dan mampu bersaing secara global. Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai profil pelajar pancasila melalui rangkaian kegiatan ekstrakurikuler dan kegiatan Project penguatan profil pelajar pancasila yang dilaksanakan di SMP Negeri 5 Kota Komba. Penelitian ini merupakan penelitian kualitatif dengan jenis kualitatif deskriptif. Data dikumpulkan dengan metode studi dokumen dan wawancara. Data dianalisis dengan proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan, nilai profil pelajar pancasila diterapkan melalui kegiatan gotong royong, kegiatan literasi dan numerasi, bimbingan agama, upacara bendera dan silaturahmi budaya sekolah. Profil pelajar pancasila sangat relevan dan bertalian dengan upaya pemerintah Indonesia dalam menerapkan pendidikan karakter di tingkat sekolah.